KESETIAAN PADA PANGGILAN DI ERA DIGITAL - Susana, Tjipto (Jurnal Orientasi Baru, 2012)
Generally, in this digital era, some concerns arise relating to assistance to young people. Mentoring process is not as easy as that done at 4 or 5 decades ago. The situation is more concerned by the monastic community which is to support the values â€œand way of life which is contrary to the valuesâ€ offered by the modern world today. The current generation does have characteristics which is different from the generation that lived in the 40s. The current generation faces challenges that make them much more difficult to persevere in the vision and commitment. By the time the situation is almost instantaneous, offering various facilities, and highly hedonic, who unwittingly caused the split of the self. This condition requires an approach that enables them to manage themselves better. Multisensory approach in learning process, self processing and spiritual exercise, as well as therapeutic community is a way offered to help them reflect and measure themselves.